A Linguagem Cinematográfica nos Games: do Gameplay à Cutscene 1 - Kremer, Karen K. (2015)
This paper aims to explore the influence of cinema in three recent video games, and to analyze how the film language presence is shownin the games, and how it has been increasingly used in the games of the most recent generation of consoles, thus creating a new form of visual communication that combines these two media in an ever more diffuse entertainment type. To this end, this paper will use the games Crysis 2(2011), I Am Alive(2012) and Max Payne 3(2012), and the films 16 Blocks (2006) and The Book of Eli(2010) in order to develop its hypotheses and formulate a concise comparative analysis.